Prevalence and Correlates of Cardiovascular Autonomic Neuropathy Among Patients with Diabetes in Uganda: A Hospital-Based Cross-sectional Study - Migisha, Richard; Agaba, David Collins; Katamba, Godfrey; Kwaga, Teddy; Tumwesigye, Raymond; Miranda, Silvia Lopez; Muyingo, Anthony; Siedner, Mark J. (Global Heart, 2020)
Cardiovascular autonomic neuropathy (CAN) is a common complication in individuals with diabetes mellitus (DM) but often overlooked in clinical practice. The burden and correlates of CAN have not been extensively studied in low-income countries, particularly in sub-Saharan Africa. Objectives: To determine the prevalence and correlates of CAN among adults in ambulatory diabetes care in southwestern Uganda. Method: We conducted a cross-sectional study among adults with diabetes from November 2018 to April 2019. CAN was assessed using the five autonomic function tests: deep breathing, Valsalva maneuver, postural index on standing, change in blood pressure during standing and diastolic blood pressure response to isometric exercise. We estimated the prevalence of CAN and fit regression models to identify its demographic and clinical correlates. Results: We enrolled 299 individuals. The mean age was 50.1 years (SD ± 9.8), mean HbA1c was 9.7 (SD ± 2.6) and 69.6% were female. CAN was detected in 156/299 (52.2%) of the participants on the basis of one or more abnormal cardiovascular autonomic reflex tests. Out of 299 participants, 88 (29.4%) were classified as early CAN while 61/299 (20.4%) and 7/299 (2.3%) were classified as definite and severe (advanced) CAN respectively. In multivariable regression models, age over 50 years (aOR 3.48, 95%CI 1.35 –8.99, p = 0.010), duration of diabetes over 10 years (aOR 4.09, 95%CI 1.78 –9.38, p = 0.001), and presence of diabetic retinopathy (aOR 2.25, 95%CI 1.16 –4.34, p = 0.016) were correlated with CAN. Conclusions: Our findings reveal a high prevalence of CAN among individuals in routine outpatient care for diabetes mellitus in Uganda. Older age, longer duration of diabetes and coexistence of retinopathy are associated with CAN. Future work should explore the clinical significance and long term outcomes associated with CAN in this region.
Keywords: Cardiovascular autonomic neuropathy; Prevalence; Diabetes